Analysis Of Chayote Puree Addition To The Quality Of Spent Layer Hens Dumplings - Pilifayo, Helga Ayunda; Holinesti, Rahmi (Universitas Negeri Padang, 2023)
The research is motivated by the use of spent layerhens which is still lacking compared to broiler chickens, because the meat is tough, so it is not enjoyed by some people. The addition of chayote puree in this research, because chayote contains has 6.7% pectin compound that is useful for thickening the texture of spent layerhens dumplings. This reseacrch aims to analyze the effect of adding chayote puree with a percentage of 0%, 15%, 25%, 35% on the quality of spent layerhens dumplings. This type of research is an experiment, using a completely randomized design (CRD) with 4 treatments and 3 repetitions. The research data was obtained from a questionnaire assessment by 3 expert panelists from the organoleptic test in October - November 2022 at the Padang State University Culinary art workshop then continued with the ANAVA Test and Duncan's Test if Fcount > Ftable. Based on the research, the best neat shape in all treatments with a score of 3.44 (quite neat), the best uniform shape in all treatments with a score of 3.33 (quite uniform), the best yellowish white color in treatment X1 with a score of 3.22 (quite uniform). (yellowish white), the best fragrant scent of dumplings in treatment X3 with a score of 3.33 (quite fragrant), the best chewy texture in treatment X3 with a score of 4.00 (chewy), the best savory taste in treatment X3 with a score of 3.78 (quite tasty), the best chayote flavor was in treatment X3 with a score of 4.00 (tasted chayote). From these results, the more chayote puree is given, the result is a chewy texture and feels chayote. The best quality test results for spent layerhens dumplings with the addition of chayote puree were treatment X3 with the addition of 35% chayote puree.